Efforts to Improve Students' Critical Thinking Skills Through Scientific Approach in Elementary School - Setyorini Murniati (JENIUS (Journal of Education Policy and Elementary Education Issues), 2023)
This research was carried out to determine teachers' application of the scientific approach to improving the critical thinking skills of Public Islamic Elementary School 4 Sukoharjo students. The subjects of this research are class VI students for the 2022/2023 academic year. The type of research is descriptive qualitative. Techniques for collecting data are direct observation, documentation, and semi-structured interviews with teachers as research subjects and students as research informants. Based on the research results, it was found that educators in the teaching process in class VI Public Islamic Elementary School 4 Sukoharjo had implemented scientific learning in teaching and learning activities, which consisted of five activity steps, namely observing, asking, trying, reasoning, and communicating. The results obtained from applying a scientific approach to learning can make students think more critically